The Theology of Vocation in Teresa of Ávila's Reformed Convent through the Lens of "Two Very Wicked Heretics" - Tigchelaar, Alisa J. (Journal of ecumenical studies, 2019)
This essay considers the life work of Catholic Reformer Teresa of Ávila through the unusual lens of the vocational theology of two key Protestant Reformers. It aims to show that although Martin Luther's and John Calvin's shared opposition to Catholic monasticism was closely connected to their notion of calling, even certain post-Tridentine monastic traditions, such as that of the founder of the Spanish Discalced Carmelites, might be particularly well understood through Protestant-Reformer articulations. The project begins with an exploration of Luther's and Calvin's theology of vocation and general implications for sixteenth-century monasticism, continuing with monastic traditions that lent themselves well to the Christian practice of vocation, both in general and among Spanish female religious. From there, Teresa of Ávila's specific vocational context is studied from within a Lutheran or Calvinist perspective. This seemingly antithetical vocabulary contributes a concluding suggestion that reevaluating seemingly paradoxical elements of early-modern-schism Christianity as potentially meaningful points of connection can contribute both to our historical understanding and to current ecumenical efforts between Catholics and Protestants.